Adolescência e divulgação não consensual de imagens íntimas: um estudo exploratório a partir de registros digitais de ocorrência - de Luca, Lucas Azzis Ferreira (2022)
Sexting consists of sending intimate images to third parties and its practice has been adopted as a mean of expression of sexuality mediated by digital technological resources, including by adolescents. However, such conduct imply in some risks, mainly because the Non-Consensual Disclosure of Intimate Images (NCDII) of the people involved can occur, which can impact the individual's mental health and even lead to suicide. Based on these arguments, the aim of this study was to characterize, through the reported cases available in a police station, victims, suspects and complaints alluding to the non-consensual disclosure of intimate images of adolescents. The research was qualitative, documental, exploratory-descriptive and cross-sectional. A documentary analysis of digital reported was carried out in a Women's Defense Police Station (DDM), located in a medium-sized city in the state of São Paulo, Brazil. The period analyzed encompassed to the reported cases of a period of approximately 12 years and the fieldwork was carried out in seven complementary stages. Initially, 22734 records were analyzed and, after applying the inclusion and exclusion criteria, 19 occurrences remained. In terms of the variables analyzed through the document, three dimensions were included: i) characteristics of the victim; ii) characteristics of the suspect; iii) characterization of the complaint. The findings showed that most victims were female adolescents, self-declared as white and, in most cases, were 13 or 14 years old when their intimate images were released. The alleged aggressors, in turn, were male in most of the documents analyzed, although occurrences were also identified in which the images had been shared by female friends of the adolescents. Attention was drawn to the fact that most of the documents did not present data that allow the identification of the alleged aggressors, which may imply in the difficulty of holding accountable for the violence committed. In addition, it was found that only one complaint was forwarded to the justice system, which suggests that cases of NCDII involving adolescents were not properly investigated. These findings are partially consistent with the international literature, but also pointed out to specificities of the Brazilian reality that deserve further investigation in the future.